Copyright on Computer Software Products in Palangka Raya City (Positive Legal Perspective and Sharia Economic Law) - Fani Aditia; Ibnu Elmi AS Pelu; Laili Wahyunita; Muhammad Faqihuddin Ibnu Sabil (Jurnal Ilmiah Al-Syir'ah, 2022)
The widespread use and sale of pirated software products to the public in Palangka Raya City, who have the potential to commit copyright infringement, motivates this research. The use and sale of software products without permission from the creator/copyright holder is piracy and an act of copyright infringement under the Copyright Law and the MUI Fatwa. This study discusses the forms and constraints in controlling Copyright on computer software products and Islamic views on the practice of buying and selling pirated computer software products. The researcher uses a statutory and conceptual approach in this sociological, juridical research. The data collection techniques in this study used literature and field studies with descriptive-analytical methods. The practice of buying and selling computer software products is legal in Islam's view. However, suppose you practice buying and selling using illegal (pirated) computer software products. In that case, the sale and purchase are considered harmful, and the law is forbidden or prohibited in Islam. The existence of free song download sites on electronic media has the potential to infringe on Copyright. I gave authors the exclusive right to use themselves and may prohibit other people without their permission from using their work primarily for commercial purposes. Free download sites that do not have permission and do not provide royalties to classify creators as copyright infringement based on the Copyright Law and ITE Law provisions. The method used in this research is legal research, which is included in empirical research. Based on the research results, the law enforcement process has not run optimally. Public legal awareness of Copyright, which is still low, and technological advances.